QUALITATIVE AND QUANTITATIVE ISSUES IN THE FORMATION OF ACCOUNTING INFORMATION IN FINANCIAL REPORTING (Scientific Conference on Multidisciplinary Studies, 2025)
In today's rapidly developing market economy, where the economy and all sectors are undergoing digital transformation, the demand for high-quality representation of accounting information in financial reporting is steadily increasing. This is because such information serves as a primary source of data for management and economic decision-making. This, in turn, highlights the relevance of the present research topic. It is well known that in order to attract external financing, creditors and potential investors are primarily interested in a company’s property and financial position.